EKSPLORASI SENYAWA OLIGOMER STILBENOID DART TUMBUHAN SLWREA MULTIFLORA BURCK - NOVIANY
Six stilbene oligomers, namely ampelopsin A, balanocarpol, a-viniferin, vaticanol G, and hopeaphenol, along with its related compound, had been isolated from acetone extract of the tree bark of Shorea mull j?ora Burck (Dipterocarpaceae). These compounds were isolated by extraction and fractionation with chromatography methods,followed by crystallization and recrystallization. The structure and the relative configuration of those compounds were determined on the basis of spectral evidence including UV, IR, MS, 'H-NMR, 13C-NMR, and 2D NMR involving 'H-'H COSY, spin decoupling, HMQC, HMBC, and NOESY experiment, as well as by comparison with reference compounds. a-Viniferin, and hopeaphenol showed cytotoxic properties with LC50= 66,9 Âµg/ml and LC5o= 191,6 jig/ml respectively, while ampelopsin A, balanocarpol, and vaticanol G was inactive (LC50>500 pg/ml) against Anemia sauna in the brine shrimp lethality test.